Induction of apoptosis in murine malignant mesothelioma cell lines: gene expression and susceptibility - Kusmiaty (Curtin University, 2003)
Malignant mesothelioma (MM) is an aggressive and highly chemo-resistant tumour of the mesothelium. Asbestos is indicated as the environmental factor most commonly associated with mesothelioma. The chemo-resistance is possibly due to impaired apoptotic mechanisms since it is known most chemotherapeutic drugs act via apoptosis. Murine MM cell lines that have been derived from tumours induced by inoculation of crocidolite asbestos into mice provide a suitable model, since both phenotypic and biological properties are closely similar to the human disease. Four murine MM cell lines were used in this study, namely ABl, AB12, AC29 and AC34. The aim of this study was to determine susceptibility of those MM cell lines to induction of apoptosis and the expression of key molecules in those cells. Many apoptosis-related genes are known, expression of some of these genes in four murine MM cell lines were investigated in this study. Gene expression was determined using conventional reverse transcription PCR (RT-PCR) and quantitated using real-time RT-PCR with SYBR-Green I detection on a Rotor-Gene 2000 (Corbett Research, N.S.W., Australia). Gene expression data was normalised against the most stable housekeeping genes as determined by the geNonn software. Susceptibility of the four murine MM cell lines to apoptosis induction was determined using cisplatin or TNF-a or IFN-y at different concentrations and at different times in the case of cisplatin. Apoptosis was assessed by a DNA laddering assay. Conventional RT-PCR results showed that all four murine MM cell lines expressed DR5, Bax, Bcl-xL, FLIP-L, c-Myc and caspase-3. Fas mRNA was detected in all cell lines except AC29. Neither FasL nor Bcl-2 was expressed in the four murine MM cell lines.Quantitation of gene expression showed that there were significant differences in Fas, DRS, Bax, Bcl-xL, c-Myc, FLIP-L and caspase-3 mRNA levels across the cell lines (P<0.05). Absence of Fas receptor in AC29 may play a role in the immunogenicity of this cell line. DNA laddering results indicated that cisplatin induced apoptosis in a dose- and time- dependent manner in those MM cell lines. Susceptibility as reflected by the minimum apoptosis-inducing dose varied among the cell lines from 1 pdml (AB12) to 10 & n l (AC34). Susceptibility to TNF-a or IFN-y also varied among the cell lines where AB12 was sensitive while AC29 was resistant to those cytokines. The AC29 and AB1 cell lines were used to examine cisplatin or TNF-a induced genes related to apoptosis, expression of Fas, caspase-3, Bax and Bcl-xL mRNA was determined using real-time RT-PCR after 6 and 24 hours induction with cisplatin or TNF-a. The results demonstrated that caspase-3 and Bax were up-regulated whereas Bcl-xL was down-regulated in AC29 after 6 hours treatment with cisplatin. Although only Bcl-xL was down-regulated in ABl after 6 hours treatment with cisplatin, the down regulation was more pronounced than in AC29. TNF-a induction of gene expression showed that Bcl-xl decreased and Fas was up-regulated significantly in AB1 after 6 hours whereas only Bcl-xL was down-regulated in AC29 after 6 hours and continued to decrease until 24 hours. The differences in gene expression changes were noticed not only between cell lines but also between two inducer agents. There were several significant results of this study. Firstly, gene expression in murine MM was seen to parallel those that have previously been described for the human disease.Therefore murine MM is likely to be a useful in in vivo model for future studies targeting apoptotic molecules. Secondly, a number of genes were not previously examined in MM were characterized in the murine model. Finally, differences in basal and induced gene expression between cell lines and inducing agents were characterized which should be followed in further studies at the protein level (eg caspase-3 activity).